New Strategies in Myeloproliferative Neoplasms: The Evolving Genetic and Therapeutic Landscape - Patel, Ami B. (Clin Cancer Res, 2016)
The classical BCR-ABL1-negative myeloproliferative neoplasms (MPNs) include essential thrombocythemia (ET), polycythemia vera (PV) and myelofibrosis (MF). While these clonal disorders share certain clinical and genetic features, MF in particular is distinct for its complex mutational landscape, severe disease phenotype and poor prognosis. The genetic complexity inherent to MF has made this disease extremely challenging to treat. Pharmacologic JAK inhibition has proven to be a transformative therapy in MPNs, alleviating symptom burden and improving survival, but has been hampered by off-target toxicities and, as monotherapy, has shown limited effects on mutant allele burden. In this review, we discuss the genetic heterogeneity contributing to the pathogenesis of MPNs, focusing on novel driver and epigenetic mutations and how they relate to combination therapeutic strategies. We discuss results from ongoing studies of new JAK inhibitors and report on new drugs and drug combinations that have demonstrated success in early preclinical and clinical trials, including Type II JAK inhibitors, anti-fibrotic agents and telomerase inhibitors.